Adiantum viscosum (Pteridaceae), a new species endemic to sclerophyllous forest of Central Chile - Cádiz-Véliz, Arón; Palma-Villalobos, Bárbara; Villarroel, Alejandro E.; Muñoz-Schick, Mélica (Phytotaxa, 2023)
Adiantum viscosum (Pteridaceae) is a new species of fern endemic to Central Chile that inhabits the sclerophyllous forest of the Valparaíso Region. Adiantum viscosum is morphologically similar to A. gertrudis and A. glanduliferum, but it differs by the presence of capitate and glandular trichomes throughout the aerial portion of the plant (pinnules, rachis, petioles and petiolules), which produce a sticky and aromatic resin. We provide a description of the species based on morphological analysis, insights about its ecology and habitat, distribution map, illustrations, a proposal for a conservation category according IUCN criteria, and a taxonomic key to the species of the genus Adiantum present in Chile.